FACTORS INFLUENCING OUTLET SELECTION OF BAKERY PRODUCTS A STUDY CONDUCTED IN KERALA - NEMAT SHEEREEN S AND ZAKKARIYA K A (EXCEL International Journal of Multidisciplinary Management Studies, 2014)
Purchase Outlets are the centres from where the customers purchase the products to satisfy their needs. Bakery products are flour-based food baked in an oven such as bread, biscuits, cookies, cake, pastries, rusk etc. This paper explores the impact of the various factors which influence the outlet selection of bakery products. There are a number of outlets available for the purchase of bakery products such as Bakery, Factory outlets, Super markets, Household units etc. The result of the study shows that outlets are selected based on certain factors such as quality, price discount, variety of products, hygiene etc. The dealers of the bakery products should give due importance to these factors in order to increase their sales and earn more profit.